2009
DOI: 10.1590/s1415-47572009000200003
|View full text |Cite
|
Sign up to set email alerts
|

Linkage disequilibrium and diversity for three genomic regions in Azoreans and mainland Portuguese

Abstract: Studies on linkage disequilibrium (LD) across the genome and populations have been used in recent years with the main objective of improving gene mapping of complex traits. Here, we characterize the patterns of genetic diversity of HLA loci and evaluate LD (D') extent in three genomic regions: Xq13.3, NRY and HLA. In addition, we examine the distribution of DXS1225-DXS8082 haplotype diversity in Azoreans and mainland Portuguese. Allele distribution has demonstrated that the São Miguel population is genetically… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2011
2011
2015
2015

Publication Types

Select...
1
1

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 29 publications
0
1
0
Order By: Relevance
“…Considering that the São Miguel population has an admixed genetic background composed mainly of Europeans and less by Jews and Africans [ 19 25 ], we compared the HFE mutations frequencies with other populations. The analysis revealed that islanders have a c.845A [p.282Tyr] frequency similar to that found in several countries in northern Europe (≈5.7%) [ 26 ], but significantly different from the reported frequencies for the Azorean island of Terceira (2.1%) [ 27 ].…”
Section: Resultsmentioning
confidence: 99%
“…Considering that the São Miguel population has an admixed genetic background composed mainly of Europeans and less by Jews and Africans [ 19 25 ], we compared the HFE mutations frequencies with other populations. The analysis revealed that islanders have a c.845A [p.282Tyr] frequency similar to that found in several countries in northern Europe (≈5.7%) [ 26 ], but significantly different from the reported frequencies for the Azorean island of Terceira (2.1%) [ 27 ].…”
Section: Resultsmentioning
confidence: 99%